2002
DOI: 10.7888/juoeh.24.313
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Public Health Nurses Regarding their Awareness of the Abilities, Skill and Knowledge Necessary to Fulfill an Occupational Health Nurse's Role, and Proposal of a New Curriculum for Occupational Nurse Specialists at the Master Level

Abstract: The areas of conduct and professional roles in occupational health nursing in Japan has not been defined as yet, even though occupational health nurses have contributed to implementing jobs related to the health examination in workplaces every year. We surveyed public health nurses regarding their awareness of the abilities, skills and knowledge necessary to fulfill an occupational health nurses' role. When answering, they became aware of deficiencies in their abilities, skills and knowledge. This was particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Research on working conditions for OHNs shows that they need more organized support to improve health management in companies 3) . It has also been proposed in a study on OHNs' role that OHN education programs should be introduced systematically 4) . Although an OHN has lesser authority on OH system in companies than an OHP, (s)he is expected to promote OH system quality.…”
Section: Introductionmentioning
confidence: 99%
“…Research on working conditions for OHNs shows that they need more organized support to improve health management in companies 3) . It has also been proposed in a study on OHNs' role that OHN education programs should be introduced systematically 4) . Although an OHN has lesser authority on OH system in companies than an OHP, (s)he is expected to promote OH system quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some reports on OHNs' activity and roles in their companies 3,4,6) , most of those concern general duties for OHNs and few studies are found to focus on duties after performing GHE. In the present survey, OHNs' tasks after GHE were centered and compared between the two types of companies whether the OHP was employed as fullor part-time.…”
Section: Discussionmentioning
confidence: 99%
“…in companies 3) . In a study on occupational health nurses' role it has been proposed that advanced education programs for OHN should be introduced systematically 4) . There is a little information on OHNs activity and role regarding GHE related health care.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this rule, OHNs do not need to be hired and the role of OHNs is unclear in the original OHSL. Hence, the social status and educational system of Japanese OHNs are insufficient (Ikushima, Ishihara, & Kawamoto, ). However, according to the Japanese Nursing Association (), the number of OHNs in Japan has increased from ~8800 in 1995 to 12,300 in 2012.…”
Section: Introductionmentioning
confidence: 99%